Slope instability triggered by climate change in periglacial areas - Francani, Vincenzo; Gattinoni, Paola; Rampazzo, Raffaele (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"The paper deals with slope instabilities triggered by the thaw of mountain permafrost related to climate change. Warming-induced permafrost degradation is likely to lead an increasing in scale and frequency of slope failures and may cause thaw settlement damages to foundations. At the same time, human settlements, infrastructural development and tourism in high mountain areas are expanding, which intensi es permafrost-related risks. The aim of the study was the understanding of the geomorphologic and climatic critical characteristics, through a hydrogeological and geomechanical modeling of mountain slopes interested by thawing permafrost. At this aim, the typical features of the areas exposed to thawing permafrost-related slope instabilities were identi ed, with reference to a speci c study area located in Italian Alps (Valmalenco, Sondrio District). Thus, considering different permafrost typology, a hydrogeological and geomechanical modeling was carried out to simulate the tenso-deformative response of the slope and to point out the effects of thawing permafrost on stability, with particular attention to the de nition of triggering thresholds and the identi cation of typical kinematisms. At this regard, modeling results showed that, because of the high water content, the kinematisms triggered by thawing permafrost are mostly debris ows and they are often concomitant with piping phenomena and liquefaction."" data-sheets-userformat=""2":15233,"3":"1":0,"10":1,"11":3,"12":0,"14":"1":2,"2":0,"15":"Arial","16":8">The paper deals with slope instabilities triggered by the thaw of mountain permafrost related to climate change. Warming-induced permafrost degradation is likely to lead an increasing in scale and frequency of slope failures and may cause thaw settlement damages to foundations. At the same time, human settlements, infrastructural development and tourism in high mountain areas are expanding, which intensi es permafrost-related risks. The aim of the study was the understanding of the geomorphologic and climatic critical characteristics, through a hydrogeological and geomechanical modeling of mountain slopes interested by thawing permafrost. At this aim, the typical features of the areas exposed to thawing permafrost-related slope instabilities were identi ed, with reference to a speci c study area located in Italian Alps (Valmalenco, Sondrio District). Thus, considering different permafrost typology, a hydrogeological and geomechanical modeling was carried out to simulate the tenso-deformative response of the slope and to point out the effects of thawing permafrost on stability, with particular attention to the de nition of triggering thresholds and the identi cation of typical kinematisms. At this regard, modeling results showed that, because of the high water content, the kinematisms triggered by thawing permafrost are mostly debris ows and they are often concomitant with piping phenomena and liquefaction.